PENGARUH LATIHAN FOOTWORK TERHADAP KELINCAHAN ATLET TENIS MEJA PTM MALAY SPORT CENTRE PEKANBARU - Muharman Suriansyah; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem in this research is the lack of agility of position movement when doing punch and act to receive the ball coming from the opponent of table tennis athlete in PTM Malay Sport Center Pekanbaru. Based on the problem, the researcher gives Footwork exercise. This study have objective to determine whether there is influence of Footwork exercise on agility of table tennis athlete in PTM Malay Sport Center Pekanbaru, so at the time of switching position in doing the punch and acting to receive the ball coming from opponents get maximum punch results. The form of this research is experimental research, with population of tennis table athletes in PTM Malay Sport Center Pekanbaru, the data in this study is the entire population of 6 people. The instrument performed in this study is the Hexagonal Obstacle Test, which aims to measure agility. After that, the data were processed by statistics, to test the normality by using lilifors test at a significant level of α (0.05).The variables of this research is footwork as independent variable (X), and agility as dependent variable(Y). The hypothesis proposed is the effect of Footwork training on agility. Based on statistical data analysis, there is an average pre-test of 8.24 and the average post-test of 7.59, then the data is normal with an increase of 0.65. Based on t test analysis yielded T-calculation equal to 4,64 and T-table 1,943, mean T calculation > T table. Thus, there is the Effect of Footwork exercise on agility at table tennis athletes in PTM Malay Sport Center Pekanbaru.KeyWords: Footwork,Agility